2014
DOI: 10.1021/bi401406p
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Cell-Penetrating Peptide Transportan 10 into a Single Vesicle by Translocating Across Lipid Membrane and Its Induced Pores

Abstract: The cell-penetrating peptide, transportan 10 (TP10), can translocate across the plasma membrane of living cells and thus can be used for the intracellular delivery of biological cargo such as proteins. However, the mechanisms underlying its translocation and the delivery of large cargo remain unclear. In this report we investigated the entry of TP10 into a single giant unilamellar vesicle (GUV) and the TP10-induced leakage of fluorescent probes using the single GUV method. GUVs of 20% dioleoylphosphatidylglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
221
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(233 citation statements)
references
References 36 publications
10
221
2
Order By: Relevance
“…wall may have a "sieving" effect with some larger peptides that would be lost in spheroplasts, requiring additional controls comparing spheroplasts and "normal" cells in other assays (18). However, even with these caveats we believe that spheroplasts provide an excellent model system compared to other alternatives to overcome size and shape limitations, such as giant unilamellar vesicles (19)(20)(21), as spheroplasts preserve a physiological bacterial membrane composition and are viable if returned to growth conditions (13,22). Moreover, although spheroplasts have generally been produced from E. coli, protocols can be adjusted to make them from strains of other species (23).…”
mentioning
confidence: 99%
“…wall may have a "sieving" effect with some larger peptides that would be lost in spheroplasts, requiring additional controls comparing spheroplasts and "normal" cells in other assays (18). However, even with these caveats we believe that spheroplasts provide an excellent model system compared to other alternatives to overcome size and shape limitations, such as giant unilamellar vesicles (19)(20)(21), as spheroplasts preserve a physiological bacterial membrane composition and are viable if returned to growth conditions (13,22). Moreover, although spheroplasts have generally been produced from E. coli, protocols can be adjusted to make them from strains of other species (23).…”
mentioning
confidence: 99%
“…Interaction of the amphipathic peptide, specifically tryptophan residues in the hydrophobic domain, with peptidoglycans are critical in the eventual internalization process [81]. Among the oldest hydrophobic peptides is transportan 10 (TP10), derived from transportan which is a chimeric peptide of the neuropeptide galanin and wasp venom mastoparan linked by a lysine chain [32,82] It was reported to sink deeply into the bilayer and cross it carrying its cargo such as green fluorescent protein (GFP) [83].…”
Section: Cell Penetrating Peptidesmentioning
confidence: 99%
“…The uptake of the peptide across the membrane can be followed using GUVs or liposomes [71,83,222]. These membrane mimics are often composed of mixture of predefined proportions of certain lipids while live cell membrane is composed of many different components in varying proportions with respect to time and space.…”
Section: Live Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamazaki and coworkers proposed a different model, based on experiments with tp10 and a single GUV composed of DOPC (80 mol%) and DOPG (20 mol%) lipids [72]. They observed that tp10 translocation and membrane pore formation appear to be two independent processes.…”
mentioning
confidence: 99%